Implementasi Undang-Undang Nomor 32 Tahun 2024 pada Stasiun Riset Bekantan Provinsi Kalimantan Selatan: Implementation of Law Number 32 of 2024 at the Proboscis Monkey Research Station, South Kalimantan Province - Utami, Suci; Hanifah, Lena; Usman, Rachmadi; Surjasni, Surjasni; Mustaqimah, Lailatul; Erniyati, Tiya; Rezeki, Amalia; Maharani, Hening Putri; Muzaki, Zaidan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Wetland ecosystems, especially mangrove forests in South Kalimantan, face serious threats from environmental degradation and land conversion, which directly affect the sustainability of the habitat of the Proboscis Monkey (Nasalis larvatus), an endangered endemic species. The implementation of Law Number 32 of 2024, which amends Law Number 5 of 1990 on the Conservation of Biological Natural Resources and their Ecosystems, is a key instrument in strengthening conservation regulations. However, the effectiveness of implementation at the local level is still hampered by low legal awareness and community participation. This Community Service Activity aims to analyze the role of non-governmental organizations (NGOs) in supporting the implementation of the Law at the Proboscis Monkey Research Station on Curiak Island, and to empower NGOs to support its implementation. The method used in this activity was a workshop and legal training, complemented by pre- and post-tests to measure participants’ level of understanding and field observations of conservation area conditions. The results of the activity showed a significant increase in participants’ legal understanding, particularly regarding the definition and substance of Law Number 32 of 2024, environmental law training, and the role of non-governmental organizations in supporting the implementation of the regulation. Through the implementation workshop, the NGO’s legal awareness of various environmental issues in conservation areas has increased. This is reflected in the post-test results, which show the increasing role, participation, and commitment of NGOs in protecting and preserving natural resources and ecosystems in the Curiak Island area, South Kalimantan.